1996
DOI: 10.1046/j.1523-1739.1996.10041013.x
|View full text |Cite
|
Sign up to set email alerts
|

Science and Management of Rocky Mountain Grizzly Bears

Abstract: The science and management of grizzly bears (Ursus arctos horribilis) in the Rocky Mountains of North America have spawned considerable conflict and controversy. Much of this can be attributed to divergent public values, but the narrow perceptions and incomplete and fragmented problem definitions of those involved have exacerbated an inherently difficult situation. We present a conceptual model that extends the traditional description of the grizzly bear conservation system to include facets of the human domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Mattson et al (1996) highlighted the importance of training the owners of natural resources in land management. Others demonstrated that major conflicts can arise if land is not properly managed (Skutsch 2000, Hellström 2001).…”
Section: Groupmentioning
confidence: 99%
“…Mattson et al (1996) highlighted the importance of training the owners of natural resources in land management. Others demonstrated that major conflicts can arise if land is not properly managed (Skutsch 2000, Hellström 2001).…”
Section: Groupmentioning
confidence: 99%
“…Frequencies of encounters is a function of how many humans are in bear habitat, their access to it, and reasons for being there. Lethality of encounters is affected by whether humans are armed, the economic value of bears (e.g., negative value for being an agricultural pest, positive value for meat and bear parts), and other cultural factors (Mattson et al 1996). Population numbers may never be accurately known, but the assumed trend in a population can be inferred by a suite of factors including changes in the spatial distribution of animals, the degree animals occupy all high quality habitat, changes in the abundance of bear sign (including sightings) and bear parts in markets, and the frequency and locations of mortalities and agricultural depredation.…”
Section: Actions For Bearsmentioning
confidence: 99%
“…Timing of research and monitoring projects should cover the range of annual variation in whatever is investigated (Mattson et al 1996). Studies of bear habitat should include occasional catastrophic events such as bamboo die-offs and the El Niño effect that causes widespread changes in the phenology of foods eaten by giant pandas and spectacled bears.…”
Section: Actions For Bearsmentioning
confidence: 99%
See 1 more Smart Citation
“…On-theground implementation of management plans for many species of carnivores, especially the larger species, requires coordinated actions among different state and Federal agencies, tribes, private landowners, and neighboring countries (Clark et al 1996a, Mattson et al 1996, Servheen and Sandstrom 1993. The formation of working groups with representation by diverse constituencies are a step in the right direction Zielinski 1995, Servheen andSandstrom 1993).…”
Section: Integrated Species Managementmentioning
confidence: 99%